p34cdc2 acts as a lamin kinase in fission yeast (The Rockefeller University Press, 1991)
The nuclear lamina is an intermediate filament network that underlies the nuclear membrane in higher eukaryotic cells. During mitosis in higher eukaryotes, nuclear lamins are phosphorylated by a mitosis- specific kinase and this induces disassembly of the lamina structure. Recently, p34cdc2 protein kinase purified from starfish has been shown to induce phosphorylation of lamin proteins and disassembly of the nuclear lamina when incubated with isolated chick nuclei suggesting that p34cdc2 is likely to be the mitotic lamin kinase (Peter, M., J. Nakagawa, M. Doree, J.C. Labbe, and E.A. Nigg. 1990b. Cell. 45:145- 153). To confirm and extend these studies using genetic techniques, we have investigated the role of p34cdc2 in lamin phosphorylation in the fission yeast. As fission yeast lamins have not been identified, we have introduced a cDNA encoding the chicken lamin B2 protein into fission yeast. We report here that the chicken lamin B2 protein expressed in fission yeast is assembled into a structure that associates with the nucleus during interphase and becomes dispersed throughout the cytoplasm when cells enter mitosis. Mitotic reorganization correlates with phosphorylation of the chicken lamin B2 protein by a mitosis-specific yeast lamin kinase with similarities to the mitotic lamin kinase of higher eukaryotes. We show that a lamin kinase activity can be detected in cell-free yeast extracts and in p34cdc2 immunoprecipitates prepared from yeast cells arrested in mitosis. The fission yeast lamin kinase activity is temperature sensitive in extracts and immunoprecipitates prepared from strains bearing temperature-sensitive mutations in the cdc2 gene. These results in conjunction with the previously reported biochemical studies strongly suggest that disassembly of the nuclear lamina at mitosis in higher eukaryotic cells is a consequence of direct phosphorylation of nuclear lamins by p34cdc2.